2020
DOI: 10.20546/ijcmas.2020.901.206
|View full text |Cite
|
Sign up to set email alerts
|

DUS Testing of Sesame (Sesamum indicum L.) Accessions Using Morphological Descriptors and Evaluation for Foliar Diseases of Sesame

Abstract: The aim of the present study is to characterize Seven hundred and twenty accessions of Sesame (Sesamum indicum L.) along with two National check varieties viz., GT-10, TKG-22 and local check variety DS-5 were characterized based on the DUS descriptors. The experiment was executed in Augmented Block Design without replication at All India Coordinated Research Project on Sesame and Network on Niger experimental plot, Main

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…This observation in sesame is in accordance with Suhasini [3]. Bhagwat Singh et al [4] and Palakshappa et al [5]. The genes determine the colour of the petal by developing or blocking of anthocyanin pigmentation.…”
Section: Morphological Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation in sesame is in accordance with Suhasini [3]. Bhagwat Singh et al [4] and Palakshappa et al [5]. The genes determine the colour of the petal by developing or blocking of anthocyanin pigmentation.…”
Section: Morphological Characterizationsupporting
confidence: 88%
“…On the basis of leaf Margin the genotypes were grouped as Entire (VRI 2, VRI 3, VRI 4, TMV 4, TMV 7, PAIYUR 1 and SVPR 1), Serrate (VRI 5). Suhasini [3] and Palakshappa et al [5] observed the similar results in sesame.…”
Section: Morphological Characterizationsupporting
confidence: 56%